2016
DOI: 10.1016/j.mgene.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cytokine and cytokine receptor gene polymorphisms on the degree of liver damage in patients with chronic hepatitis C

Abstract: Hepatic fibrosis may be the result of repetitive injury to hepatocytes caused by HCV infection and the immune response to it. Cytokines regulate the inflammatory response to injury and modulate hepatic fibrogenesis. Single nucleotide polymorphisms (SNPs) located in cytokine genes may influence the cytokine expression and secretion that may contribute to hepatic fibrogenesis in HCV infection. The aim of this study was to determine the genotype of 22 SNPs found in the genes of 13 cytokines/cytokine receptors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Furthermore, other studies have also found no relationship between these polymorphisms in the TNF and IL10 genes and different stages of the disease [ 16 ]. On the other hands, gene variants of cytokines/receptors may influence liver damage in patients chronically infected by HCV genotype [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have also found no relationship between these polymorphisms in the TNF and IL10 genes and different stages of the disease [ 16 ]. On the other hands, gene variants of cytokines/receptors may influence liver damage in patients chronically infected by HCV genotype [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that individuals with the GG genotype had significantly higher liver stiffness and liver cirrhosis than individuals with GA or AA genotypes [ 54 ]. However, Moreira et al and Yee et al reported a protective role for high fibrosis stages in homozygous GG and an association between this specific polymorphism and higher fibrosis stages [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1 β and IL‐1RN gene polymorphisms were reported to be associated with the progression of liver fibrosis in CHC infection . IL‐1β_511 “TT” genotype has been shown to be associated with liver cirrhosis and IL1B‐511 “TC” genotype is found to be associated with the stage of liver damage during HCV genotype 1 infection .…”
Section: Discussionmentioning
confidence: 99%